MENINGKATKAN KEMAMPUAN GERAK TARI SARONDE MELALUI METODE DRILL AND PRACTICE PADA SISWA KELAS V SEKOLAH DASAR - Rahmatia Tulenan; Wiwy Triyanty Pulukadang; Mimy Astuty Pulukadang; La Ode Karlan; Rustam I Husain (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study addresses the problem of whether the implementation of the Drill and Practice method can improve students’ ability in performing Saronde dance movements among fifth-grade students at SDN 29 Kota Selatan, Gorontalo. This research employed a Classroom Action Research (CAR) design consisting of two cycles. Data were collected through observation, tests, and documentation techniques. The initial observation indicated that students had not yet been taught Saronde dance by the teacher, resulting in low performance ability. During the implementation of Cycle I, the number of students who achieved competency in Saronde dance movements was 3 students (27%) in the first meeting, which increased to 5 students (45%) in the second meeting. In Cycle II, further improvement was observed, with 8 students (73%) achieving competency in the first meeting, and eventually reaching 11 students (100%) in the second meeting. Based on these findings, it can be concluded that the Drill and Practice method effectively improves students’ ability in performing Saronde dance movements among fifth-grade students at SDN 29 Kota Selatan, Gorontalo.